Curriculum Quality and Personal Resources as Predictors of Subjective Employability among TESOL Students and Graduates in Cambodia - Hornmann Banh (MASI Mandiri Edukasi, 2026)
This study examines how TESOL program quality and personal resources predict graduates’ perceived employability in one program in the Cambodian private university. A cross-sectional survey of TESOL students and recent graduates (n = 263) measured five curriculum factors and four personal factors against five indicators of subjective employability. Correlation and regression analyses revealed that all curriculum and personal factors were positively associated with self-perceived employability. Practice-intensive curriculum features (teaching practicum, peer teaching) and personal resources (teaching self-efficacy, outcome expectations) showed particularly strong links with employability outcomes. In a combined model, personal factors – especially work adaptation, social capital, and outcome expectations – accounted for substantially more variance in employability perceptions than curriculum factors. Because the data are cross-sectional, self-reported, and drawn from a single institution, the findings indicate associations rather than causation and may not generalize to other TESOL programs or contexts. The findings suggest that while high-quality training contributes to graduates’ career readiness, their adaptability, professional networks, and future-oriented outlook ultimately play a more decisive role in how employable they feel. The study recommends enhancing authentic teaching practice, career guidance, and networking opportunities in TESOL programs to improve graduate employability.